PENGEMBANGAN MEDIA TUTORIAL PEMBELAJARAN MATA KULIAH MEDIA FOTOGRAFI PEMBELAJARAN - Pradana, Mochamad Desta (Institut Agama Islam Negeri Kediri, 2018)
Abstract: One of the efforts to solve learning problems is by developing instructional resources. One of them is instructional tutorial. Based on the field observation, subject of photo media for Instruction (photography) in graduate program PBA of STAIN Kediri still employes instructional media (utilization). Thus, there is a need to develop media of instructional tutorial (by desaign) in order to overcome errors in delivering instructional messages. The aim of this study is to produce instructional media of subject of photo media for Instruction (photography) in the form of tutorial, lecturer guidance and students' guidance which is expected to be able to help students gain knowledge of facts, concepts, and proper shooting procedures. The tutorial media is developed in terms of the study of the instructional technology which is based on the ADDIE model. The ADDIE model is a systematic instructional design model consisting of five phases: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Furthermore, the product of the development of the instructional interactive multimedia will be evaluated. There are six steps in the evaluation phase: (1) judgement of the matter expert/ the material expert, (2) judgement of the design expert, (3) judgement of the media expert, (4) individual trials, (5) small group trials, (6) large group trials/ field trials. The result of expert validation for this instructional media tutorial indicates that it is properly designed, 73%. The result of media expert validation shows that it is very properly designed, 83%. The result of design expert validation shows that it is very properly designed, 82%. Personal validation is on the proper category, 70%. Result of small group validation is on proper category, 70%. Moreover, the result for big group test or field test is on the very proper category, 95%. Suggestion proposed related with the use and developing of media tutorial is (1) lecturers should be more creative and innovative in delivering instructional messages contained in this tutorial in order to make learning to be more attractive, fun, and creative, (2) there is a need to develop instructional media for subject of photo media instruction (photography) or other subjects, (3) the use of designed in media tutorial should be more interesting to make learning more interactive and interesting. Abstrak: Salah satu upaya untuk memecahkan masalah pembelajaran adalah dengan mengembangkan sumber daya pembelajaran. Salah satunya adalah tutorial pembelajaran. Berdasarkan observasi lapangan, subjek media foto untuk Pembelajaran (fotografi) pada program pascasarjana PBA STAIN Kediri masih menggunakan media pembelajaran (pemanfaatan). Oleh karena itu, perlu dikembangkan media pembelajaran (by desaign) untuk mengatasi kesalahan penyampaian pesan pembelajaran. Penelitian ini bertujuan untuk menghasilkan media pembelajaran mata pelajaran media foto untuk Pembelajaran (fotografi) berupa tutorial, bimbingan dosen dan bimbingan mahasiswa yang diharapkan dapat membantu mahasiswa memperoleh pengetahuan tentang fakta, konsep, dan pemahaman yang benar. prosedur pemotretan. Saran yang diajukan terkait pemanfaatan dan pengembangan media tutorial adalah (1) dosen harus lebih kreatif dan inovatif dalam menyampaikan pesan-pesan pembelajaran yang terkandung dalam tutorial ini agar pembelajaran menjadi lebih menarik, menyenangkan, dan kreatif, (2) ada perlunya pengembangan media pembelajaran untuk mata pelajaran media foto (fotografi) atau mata pelajaran lainnya, (3) penggunaan media pembelajaran yang dirancang harus lebih menarik agar pembelajaran lebih interaktif dan menarik.